Adipose tissue fatty acid metabolism in insulin-resistant men. - Bickerton, A; Roberts, R; Fielding, B; Tornqvist, H; Blaak, E; Wagenmakers, A; Gilbert, M; Humphreys, S; Karpe, F; Frayn, K (2008)
AIMS/HYPOTHESIS: Increased NEFA production and concentrations may underlie insulin resistance. We examined systemic and adipose tissue NEFA metabolism in insulin-resistant overweight men (BMI 25-35 kg/m2). METHODS: In a cohort study we examined NEFA concentrations in men in the upper quartile of fasting insulin (n = 124) and in men with fasting insulin below the median (n = 159). In a metabolic study we examined NEFA metabolism in the fasting and postprandial states, in ten insulin-resistant men and ten controls. RESULTS: In the cohort study, fasting NEFA concentrations were not significantly different between the two groups (median values: insulin-resistant men, 410 micromol/l; controls, 445 micromol/l). However, triacylglycerol concentrations differed markedly (1.84 vs 1.18 mmol/l respectively, p < 0.001). In the metabolic study, arterial NEFA concentrations again did not differ between groups, whereas triacylglycerol concentrations were significantly higher in insulin-resistant men. Systemic NEFA production and the release of NEFA from subcutaneous adipose tissue, expressed per unit of fat mass, were both reduced in insulin-resistant men compared with controls (fasting values by 32%, p = 0.02, and 44%, p = 0.04 respectively). 3-Hydroxybutyrate concentrations, an index of hepatic fat oxidation and ketogenesis, were lower (p = 0.03). CONCLUSIONS/INTERPRETATION: Adipose tissue NEFA output is not increased (per unit weight of tissue) in insulin resistance. On the contrary, it appears to be suppressed by high fasting insulin concentrations. Alterations in triacylglycerol metabolism are more marked than those in NEFA metabolism and are indicative of altered metabolic partitioning of fatty acids (decreased oxidation, increased esterification) in the liver.